Walter B. Wriston with his granddaughter, Barbara Catherine Quintal (Tufts Archival Research Center, 2008)
6.9 x 4.9. This picture was taken on the Wriston Farm in Connecticut. This date is approximate. The print and digital image were created from 'File3123' from the CD titled 'Walter B. Wriston Photographs - CD 6'.